Prolonged culture of human islets induces ER stress - Erbel, Saskia; Reers, Christina; Nawroth, Peter Paul; Ritzel, Robert (Experimental and clinical endocrinology & diabetes, 2010)
Type 2 diabetes (T2D) is characterized by islet dysfunction and beta-cell deficiency caused by apoptosis. One mechanism underlying induction of beta-cell apoptosis is stress in the endoplasmic reticulum (ER). Isolated human islets are a frequently used model to examine islet pathophysiology in T2D. Therefore it is important to establish how function and beta-cell turnover of human islets change in culture. Islets from four organ donors were cultured over four weeks. At 0, 1, 2, 3 and 4 weeks aliquots of islets were used for analysis of a) islet-cell turnover (replication by Ki-67 and apoptosis by TUNEL staining), b) the ER stress level (CHOP and phospho-eIF2α staining), c) fractional beta-cell content (insulin staining) and d) islet function (2 h static incubation). Culture duration positively correlated to replication (p=0.03) and negatively correlated to apoptosis (p=0.003). In comparison to islets in situ islet cell turnover is accelerated (>10-fold). The ER stress level was stable during the first three weeks, but showed a sharp increase (p<0.05) at four weeks. The fractional beta-cell content increased from 29±2% to 41±2% (p=0.0004). Islet function improved (p<0.0001). In conclusion, isolated human islets may be used for in vitro experiments for up to three weeks. During this time islet function and islet-cell turnover are stable. If islet culture is extended beyond three weeks ER stress may impair islet viability. Studies analyzing the pathophysiology of human T2D at the level of the endocrine pancreas need to confirm results obtained with isolated human islets by analysis of primary human pancreatic tissue.